1996
DOI: 10.1007/bf00817919
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of26Al-labelled aluminium citrate and aluminium hydroxide in volunteers

Abstract: A study was undertaken to determine the fraction of ingested aluminium taken up by two male volunteers, following their ingestion of either aluminium citrate or aluminium hydroxide. In addition, the effects of simultaneous citrate ingestion on the gastrointestinal absorption of aluminium from its hydroxide was studied. Volunteers received three oral doses of 26Al-labelled aluminium compound in water. The doses were administered directly into the stomach using a paediatric feeding tube. Blood samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 13 publications
0
41
0
1
Order By: Relevance
“…67 Gallium as a tracer for Aluminum 67 Ga is readily available because it is used in routine clinical diagnoses (Priest et al 1995(Priest et al , 1996Radunovic et al 1997a, b). It is a cheap and readily available isotope in Australia (ANSTO, Lucas Heights, NSW) and elsewhere.…”
Section: Kinetics Of Growthmentioning
confidence: 98%
See 2 more Smart Citations
“…67 Gallium as a tracer for Aluminum 67 Ga is readily available because it is used in routine clinical diagnoses (Priest et al 1995(Priest et al , 1996Radunovic et al 1997a, b). It is a cheap and readily available isotope in Australia (ANSTO, Lucas Heights, NSW) and elsewhere.…”
Section: Kinetics Of Growthmentioning
confidence: 98%
“…A few clinical studies have attempted to measure Al uptake using 26 Al in mammalian systems (humans: Priest et al 1995Priest et al , 1996mice: Radunovic et al 1997a;rats: Radunovic et al 1997b;Zafar et al 1997, review: Gupta et al 2005. Some of these studies attempted to use 67 Ga as a tracer for Al Biometals (2008) 21:379-393 381 and had the resources to be able to do 26 Al/ 67 Ga double labelling experiments.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A number of researches have shown that aluminium intake with drinking water can make for dementia evolvement and Alzheimer syndrome [9,8,34,35]. Such effect can be explained by the fact that aluminium salts contribute to inflammatory cytokine activation in cerebrum [12].…”
Section: Aluminium Bioavailability and Toxicitymentioning
confidence: 99%
“…The biological effects of this active chemical element in humans is currently being studied using 26Al, whose 750,000 year half life is more amenable to biological experimentation that the next longest lived isotope at 6.5 minutes: 29Al. (Barker et al 1992;Day et al 1994;Harris et al 1996;Jouhanneau et al 1993;Priest et al 1995;Priest et al 1996) Kislinger et al 1997;Steinhausen et al 1996).…”
Section: Elemental Tracingmentioning
confidence: 99%